Experimental and Stress-Strain Equation Investigation on Compressive Strength of Raw and Modified Soil in Loess Plateau - Youchao Zhang; Yihong Wang; Nana Zhao; Tianya Wang (Advances in Materials Science and Engineering)
As a special kind of soil is widely distributed in Loess Plateau of northwest China, it is difficult to use for growing crops and has poor structural property. According to local arid climate, the best utilization of the soil is as earthen construction material and it has been used for thousands of years. To research and improve the mechanical properties, the study investigates the response of soil with cement, lime, sand, and straw as admixtures to compressive loading. The influence on compressive strength and ductility of additives in different proportions is compared and analysed. The experimental data is also used for the formulation of dimensionless and generalized models describing the raw soil and modified soil’s full stress-strain response. The models can be applied to soil and modified soil in Loess Plateau with variable strength and deformation characteristics and therefore may be exploited for earthen construction design and nonlinear structural analyses.